2014
DOI: 10.1016/j.yjmcc.2013.11.010
|View full text |Cite
|
Sign up to set email alerts
|

HASF is a stem cell paracrine factor that activates PKC epsilon mediated cytoprotection

Abstract: Despite advances in the treatment of acute tissue ischemia significant challenges remain in effective cytoprotection from ischemic cell death. It has been documented that injected stem cells, such as mesenchymal stem cells (MSCs), can confer protection to ischemic tissue through the release of paracrine factors. The study of these factors is essential for understanding tissue repair and the development of new therapeutic approaches for regenerative medicine. We have recently shown that a novel factor secreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Sfrp2 promotes the protection of cardiomyocytes by binding to the pro-apoptotic protein Wnt3a 29 . In contrast, HASF prevents cardiomyocyte cell-death through PKCε 31 . As noted in a recent editorial HASF has a number of novel features as a cytoprotective factor 136 .…”
Section: Emerging Concepts In Paracrine Mechanisms: Temporal and Spatmentioning
confidence: 89%
See 1 more Smart Citation
“…Sfrp2 promotes the protection of cardiomyocytes by binding to the pro-apoptotic protein Wnt3a 29 . In contrast, HASF prevents cardiomyocyte cell-death through PKCε 31 . As noted in a recent editorial HASF has a number of novel features as a cytoprotective factor 136 .…”
Section: Emerging Concepts In Paracrine Mechanisms: Temporal and Spatmentioning
confidence: 89%
“…Analysis of the heart tissue showed that HASF reduced the number of TUNEL positive nuclei as well as inhibiting caspase activation and mitochondrial pore opening. The cytoprotective effects of HASF were lost in mice lacking PKCε 31 .…”
Section: Effects Of the Paracrine Factorsmentioning
confidence: 97%
“…Hmox1 encodes heme oxygenase 1 (alias HSP37), an essential antioxidant heme-catabolism enzyme found to be cytoprotective against H 2 O 2 - induced oxidative-stress in lens epithelial cells (76). Trex1 encodes an ER-associated 3′-exonuclease implicated in suppressing innate immune responses (77) and 1190002N15Rik codes for a secreted Golgi protein (GoPro49) with cytoprotective properties (78). Taken together, the differential regulation of many genes unrelated to the UPR suggests that additional stress-response mechanisms may operate during Mip -related cataractogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Third, 1190002N15Rik was the only gene down-regulated in the Mip−/− lens and the Lop/+ lens at both P1 and P7 [24]. 1190002N15Rik encodes a secreted Golgi protein (GoPro49), also known as deleted in autism protein 1 homolog (DIA1) or hypoxia and Akt-induced stem cell factor (HASF), that possesses cytoprotective and anti-apoptotic properties; however, its role in the lens secretory pathway is unclear [3840]. Finally, Hspb1 was moderately down-regulated in the Mip−/− lens at P1 and strongly down-regulated in the Lop/+ lens at P1 and P7.…”
Section: Discussionmentioning
confidence: 99%